Penerapan Audit Sistem Informasi Pendaftaran Siswa Menggunakan Cobit 4.1 - Puteri Diyana; Richa Orellia; Arisma Yulistiani (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The registration system at BLK Surakarta appears to be experiencing data redundancy which needs to be addressed through in-depth analysis. The student registration process is integrated into the system, but there are still deficiencies in data management which results in frequent data duplication or errors. This research uses Cobit 4.1 as a framework for auditing the registration system at BLK Surakarta, with a focus on the Delivery and Support subdomain (DS 10 and DS11). The main objective is to assess the maturity level of the IT processes implemented at BLK Surakarta and provide recommendations for improvement. The research results show the need for BLK Surakarta to carry out regular system performance evaluations, involving parties responsible for identifying and overcoming problems that arise, in order to ensure optimal system conditions. Evaluation in Domain 10 Delivery & Support shows a current maturity level of 3.27, while in Domain 11 Delivery & Support, the maturity level is 3.31. However, it was found that the process of managing payment data for new student registration was less than optimal due to limited tools available.